Effects of the coupling agent structure on the adhesion of recycled polystyrene wood flour composites: Thermal degradation kinetics and thermodynamics parameters. (September 2016) - Poletto, Matheus
Recycled polystyrene wood flour composites were developed with three different polystyrene maleic anhydride oligomers used as coupling agents. The thermal properties, morphology, kinetics, and thermodynamic parameters were investigated. The use of oligomers clearly improves the interfacial adhesion with the polymer matrix and increases the thermal stability of the composites. The oligomers with higher maleic anhydride content tend to reduce the composite thermal stability, while oligomers with intermediate quantities of maleic anhydride groups tend to promote a higher composite thermal stability. The thermodynamic results showed that the composite without coupling agent presented the lowest entropy value, which indicates that the thermal decomposition in this composite is slow. However, the entropy values and frequency factor increased when coupling agents were used. The addition of coupling agents likely changed the state near to the thermodynamic equilibrium by causing structural disorder, in the system increasing the treated composite reactivity.